Isorhamnetin alleviates lipopolysaccharide-induced inflammatory responses in BV2 microglia by inactivating NF-κB, blocking the TLR4 pathway and reducing ROS generation - Kim, Shin Young (Int J Mol Med, 2019)
Isorhamnetin, which is a flavonoid predominantly found in fruits and leaves of various plants, including Hippophae rhamnoides L. and Oenanthe javanica (Blume) DC, is known to possess various pharmacological effects. However, the anti-inflammatory potential of isorhamnetin remains poorly studied. Therefore, the present study aimed to investigate the inhibitory potential of isorhamnetin against inflammatory responses in lipopolysaccharide (LPS)-stimulated BV2 microglia. To measure the effects of isorhamnetin on inflammatory mediators and cytokines, and reactive oxygen species (ROS) generation, the following methods were used: cell viability assay, griess assay, ELISA, reverse transcriptase-polymerase chain reaction, flow cytometry, western blotting and immunofluorescence staining. The results revealed that isorhamnetin significantly suppressed LPS-induced secretion of pro-inflammatory mediators, including nitric oxide (NO) and prostaglandin E(2), without exhibiting significant cytotoxicity. Consistent with these results, isorhamnetin inhibited LPS-stimulated expression of regulatory enzymes, including inducible NO synthase and cyclooxygenase-2 in BV2 cells. Isorhamnetin also downregulated LPS-induced production and expression of pro-inflammatory cytokines, such as tumor necrosis factor-α and interleukin-1β. The mechanism underlying the anti-inflammatory effects of isorhamnetin was subsequently evaluated; this flavonoid inhibited the nuclear factor (NF)-κB signaling pathway by disrupting degradation and phosphorylation of inhibitor κB-α in the cytoplasm and blocking translocation of NF-κB p65 into the nucleus. In addition, isorhamnetin effectively suppressed LPS-induced expression of Toll-like receptor 4 (TLR4) and myeloid differentiation factor 88. It also suppressed the binding of LPS with TLR4 in BV2 cells. Furthermore, isorhamnetin markedly reduced LPS-induced generation of ROS in BV2 cells, thus indicating a strong antioxidative effect. Collectively, these results suggested that isorhamnetin may suppress LPS-mediated inflammatory action in BV2 microglia through inactivating the NF-κB signaling pathway, antagonizing TLR4 and eliminating ROS accumulation. Further studies are required to fully understand the anti-inflammatory effects associated with the antioxidant capacity of isorhamnetin; however, the findings of the present study suggested that isorhamnetin may have potential benefits in inhibiting the onset and treatment of neuroinflammatory diseases.